Could tight junctions regulate the barrier function of the aged skin - Svoboda, Marek; Bílková, Zuzana; Muthný, Tomáš (Journal of dermatological science, 2016)
The skin is known to be the largest organ in human organism creating interface with outer environment. The skin provides protective barrier against pathogens, physical and chemical insults, and against uncontrolled loss of water. The barrier function was primarily attributed to the stratum corneum (SC) but recent studies confirmed that epidermal tight junctions (TJs) also play important role in maintaining barrier properties of the skin. Independent observations indicate that barrier function and its recovery is impaired in aged skin. However, trans-epidermal water loss (TEWL) values remains rather unchanged in elderly population. UV radiation as major factor of photoageing impairs TJ proteins, but TJs have great self-regenerative potential. Since it may be possible that TJs can compensate TEWL in elderly due to its regenerative and compensatory capabilities, important question remains to be answered: how are TJs regulated during skin ageing? This review provides an insight into TJs functioning as epidermal barrier and summarizes current knowledge about the impact of ageing on the barrier function of the skin and epidermal TJs.
Keywords: Skin Absorption; Skin Aging; Aging; Epidermis; epidermis; stárnutí kůže; ultrafialové záření; perspiratio insensibilis; kožní absorpce; věkové faktory; stárnutí; zvířata; Humans; Tight Junctions; permeabilita; Permeability; Water Loss, Insensible; Ultraviolet Rays; Age Factors; těsný spoj; lidé; Animals